Dispersed Nickel Cobalt Oxyphosphide Nanoparticles Confined in Multichannel Hollow Carbon Fibers for Photocatalytic CO2 Reduction - Wang, Yan; Wang, Sibo; Lou, Xiong Wen (David) (Angewandte Chemie International Edition, 2019)
Materials for high‐efficiency photocatalytic CO2 reduction are desirable for solar‐to‐carbon fuel conversion. Herein, highly dispersed nickel cobalt oxyphosphide nanoparticles (NiCoOP NPs) were confined in multichannel hollow carbon fibers (MHCFs) to construct the NiCoOP‐NPs@MHCFs catalysts for efficient CO2 photoreduction. The synthesis involves electrospinning, phosphidation, and carbonization steps and permits facile tuning of chemical composition. In the catalyst, the mixed metal oxyphosphide NPs with ultrasmall size and high dispersion offer abundant catalytically active sites for redox reactions. At the same time, the multichannel hollow carbon matrix with high conductivity and open ends will effectively promote mass/charge transfer, improve CO2 adsorption, and prevent the metal oxyphosphide NPs from aggregation. The optimized hetero‐metal oxyphosphide catalyst exhibits considerable activity for photosensitized CO2 reduction, affording a high CO evolution rate of 16.6 μmol h−1 (per 0.1 mg of catalyst). Nickel cobalt oxyphosphide nanoparticles (NiCoOP NPs) were confined in multichannel hollow carbon fibers (MHCFs) for CO2 photoreduction. The highly dispersed mixed metal oxyphosphide NPs provide abundant active sites for photoreduction, while the multichannel hollow carbon support prevents NPs from aggregation and facilitates electron‐hole transport, thus enabling efficient CO2 reduction under visible light.